Chika's House - Okoye, Ifeoma (Heinemann Educational Books (Nigeria) Ltd, 1995)
Part of a series of readers for young African students and consisting of stories from all over Africa, the Level 1 starters are picture books for children who have just begun to read for themselves. In this story Chika gets lost. How can he find his way home?
Keywords: Juvenile literature-English Language readers-Primary-Fiction-Nigeria (English)